Pharmacokinetic Analysis of Huangqi Guizhi Wuwu Decoction on Blood and Brain Tissue in Rats with Normal and Cerebral Ischemia-Reperfusion Injury by Microdialysis with HPLC-MS/MS - Zheng HZ; Shen X; He YY; Yan XL; Wang SX; Yu AM; Wang LS (Dove Medical Press, 2020)
Hao-Zhen Zheng, Xiao Shen, Ying-Ying He, Xiang-Li Yan, Sheng-Xin Wang, Ai-Ming Yu, Li-Sheng Wang College of Chinese Materia Medica, Guangzhou University of Chinese Medicine, Guangzhou 51006, Guangdong, People’s Republic of ChinaCorrespondence: Li-Sheng Wang Tel +86 20-39358290Email wlis68@126.comObjective: The aim of our research was to analyze and compare the pharmacokinetics of paeoniflorin, calycosin, calycosin-7-o-β-d-6-glucoside, and 6-gingerol in the blood and brain tissue of normal and cerebral ischemia-reperfusion injury rats by HPLC-MS/MS method.Methods: The blood and brain tissue samples of normal and middle cerebral artery occlusion (MCAO) rats were compared. The blood and brain tissue samples were collected by using microdialysis technique. The concentrations of paeoniflorin, calycosin, calycosin-7-o-β-d-6-glucoside, and 6-gingerol in blood and brain tissues were determined by the HPLC-MS/MS internal standard method.Results: Compared with the normal group, the model group after the administration of the Huangqi Guizhi Wuwu Decoction showed that Cmax blood, AUC0-t blood, and AUC0-inf blood of paeoniflorin were increased, CLblood, t1/2 brain, and Vbrain of paeoniflorin were decreased; Cmaxblood, AUC0-tblood, AUC0-infblood, and average residence time (MRTbrain) of calycosin-7-o-β-d-6-glucoside were decreased and the CLblood and Cmax brain of calycosin-7-o-β-d-6-glucoside were increased; Cmax blood of calycosin was decreased, Vblood and Vbrain of calycosin were increased; Cmax blood, AUC0-t blood, AUC0-inf blood, and MRTbrain of 6-gingerol were decreased, CLblood of 6-gingerol was increased.Conclusion: This method is simple, rapid, and sensitive. It is suitable for the pharmacokinetic study of Huangqi Guizhi Wuwu Decoction in the blood and brain tissue of rats. Cerebral ischemia-reperfusion injury increased the content of paeoniflorin, calycosin, calycosin-7-o-β-d-6-glucoside, and 6-gingerol in the blood, affecting the clearance rate of paeoniflorin in the brain, the detention time of calycosin-7-o-β-d-6-glucoside and the 6-gingerol in the brain. In normal and cerebral ischemia-reperfusion rats, the content of paeoniflorin and 6-gingerol in the blood was higher than that in brain tissue, while the content of calycosin, calycosin-7-o-β-d-6-glucoside in the brain tissue was higher than that in blood, suggesting that calycosin and calycosin-7-o-β-d-6-glucoside have brain targeting properties.Keywords: Huangqi Guizhi Wuwu Decoction, microdialysis, paeoniflorin, calycosin-7-o-β-d-6-glucoside, calycosin, 6-gingerol, pharmacokinetics